The prevalence and economic importance of nematode infection in goats in Gweru District, Zimbabwe - Boomker, Jacob Diederik Frederik (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Tropical Diseases))--University of Pretoria, 2009.